Helium Signatures of Natural Gas From the Dongpu Sag, Bohai Bay Basin, Eastern China - Ni, Chunhua; Wu, Xiaoqi; Liu, Quanyou; Zhu, Dongya; Yang, Fan; Meng, Qingqiang; Xu, Huiyuan; Xu, Shutang; Xu, Tianwu (Frontiers in Earth Science, 2022)
The Dongpu Sag is one of the important areas for oil and gas exploration in the Bohai Bay Basin, eastern China, and natural gas from different strata in the sag contain a certain amount of helium, with the geochemical characteristics and the implications being weakly studied. Based on the analyses of the helium contents and isotopic ratios (3He/4He, 40Ar/36Ar, CH4/3He, and CO2/3He) of natural gas, the abundance and origin of helium as well as the correlation with CH4 and CO2 are investigated. The results indicate that, natural gas samples from the Dongpu Sag display the helium contents of 0.0031%‒0.0217% and 3He/4He ratios of 0.148×10-7‒11.986×10-7, and the CH4/3He and CO2/3He ratios range from 3.7×109 to 1.8263×1012 and from 0.05×109 to 35.04×109, respectively. Natural gas in the sag is helium depleted and extremely depleted, with the average helium content of 0.0133%. The helium reserves in the total gas reserves are 18.38×106 m3, meeting the standard of small helium gas field. The helium is mainly crustal which has been mixed by a small amount of mantle-derived helium, whose proportion ranges from 0.01% to 10.72% with an average of 2.39%. Helium-related isotopic ratios of natural gas from the Dongpu Sag are consistent with those from other areas of the Bohai Bay Basin, suggesting crust-mantle mixed sources. Several gas samples from members 2 and 3 of the Shahejie Fm. contain an insignificant amount of mantle-derived helium, displaying the characteristics consistent with natural gas from typical cratonic basins.